Financing Micro-Enterprises with Islamic Financial Instruments in Nigeria: A Way Forward - Adamu Abubakar Muhammad; Hamza Abubakar Hussaini; Ibrahim Dahiru Idriss; Yakubu Zulaihat Muhammed (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2023)
The purpose of this article was to examine how Islamic financial instruments aid micro- businesses in Nigeria by providing funding. The micro-enterprise sector offers prospects for economic growth, investment, and job creation, but because it lacks direct access to capital, it is mainly underdeveloped. This study identifies the potential of Islamic financial instruments as a source of funding for micro-enterprises by combining qualitative and quantitative research approaches in a novel way to comprehend the current financing structures. A survey of Nigerian micro-businesses is one of the research's efforts, along with a number of semi-structured interviews and document analysis. The findings of the research suggest that the majority of microenterprises are unaware of or have no access to Islamic financial instruments, and there is a need for better education and awareness regarding these instruments. Additionally, the research paper concludes with recommendations for policymakers and practitioners on how to increase the use of Islamic financial instruments in Nigeria to promote micro-enterprises for economic growth and development.